Impact of a Non-Playable Character on Player Experience and Performance in VR Games - Lêu, Matheus O.; Nunes, Fatima L. S.; Peres, Fabiana; Teixeira, João Marcelo (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2025)
Serious games in virtual reality are valuable tools for therapy but can feel intrusive when users lack experience with the technology or must contend with excessive hardware—particularly head-mounted displays (HMDs). Introducing social elements, such as non-player characters (NPCs), into therapeutic games may help make the experience more comfortable and less invasive for the user. In this work, we implement and evaluate the effects of an NPC within a virtual reality serious game. The developed game encourages arm movements and features a fox avatar, which offers contextual tips and accompanies the player throughout the therapy session. Data analysis revealed that, although players’ performance was modestly impaired by distraction from the NPC, nearly all participants reported that the gameplay felt more enjoyable with the character’s presence. Additionally, specialist testing highlighted positive aspects of the experience and emphasized the NPC’s potential to enhance player motivation in therapeutic contexts. These findings can inform future research aimed at designing interactions that foster a more natural rapport between player and NPC—free from time pressure—and thus enable a more immersive and comfortable therapeutic experience.